DISTRIBUTIVE-TRANSFORMATIONAL METHOD OF STUDYING THE SEMANTIC STRUCTURE OF THE VERB - Abdurakhmanov Fakhriddin Israilovich (Scholar Express Journal, 2023)
3 The article describes the semantic representations that could be derived from the interpretation of actantial verb structures that followed Fillmore called frames. In the article it is assumed that in the semantic interpretation of distributive-transformational scheme communique between frames minimal interpretation of case determines the value of each of the actants. To determine the value of case, it is sufficient and necessary to carry word of this case forms a distributive basis, transformational and call frame corresponding to a segment of the interpretation of the noun.
Keywords: Distributive-transformational scheme; the frame; the value of case, actant; semantic class